A study on 2-(2’-hydroxyphenyl) benzoxazoles derivatives as potential organic UV filters, Part I - da Silva, Jameson Ferreira (2023)
Damage resulting from the incidence of ultraviolet (UV) radiation on the skin is common nowadays, with UVB (290-320 nm) and UVA (320-400 nm) radiation responsible for photoaging, sunburn and carcinogenesis. For this reason, sunscreens represent products of growing interest to prevent such damage. However, there are few organic filters marketed worldwide with photostability and effectiveness at wavelengths greater than 340 nm (long UVA), which justifies the exploration for new compounds. In this work, we determined the photostability and sun protection factor (SPF) of three 2-(2’-hydroxyphenyl)benzoxazole derivative dyes in order to develop new organic UV filters. UV-vis spectrophotometry has high level of reproducibility when compared with in vivo human clinical methods. Solubility determinations were performed in different solvents. The compounds absorbed UVA and UVB radiation, with maximum absorption wavelengths ranging from 336 to 374 nm. Photostability was evaluated using a solar simulator (3 J.m2.s-1 UVA radiation) for a maximum of 3 h. The 2-(amino-2’-hydroxyphenyl) benzoxazoles showed higher photostability than the acetylated derivative under the evaluated conditions. The three benzoxazoles presented SPF values of around 40 and preliminary results indicate that they show suitable properties to act as good chemical filters in photoprotective formulations.